Shoe Lasting With Manual Techniques - Abimanyu Yogadita Restu Aji (Institut Seni Indonesia Yogyakarta, 2022)
Shoe last is a foot imitation used in the process of making footwear. The shoe last can be plastic, aluminum, or wood. Footwear last can be made of wood with manual techniques. The making of shoelast using manual techniques is thought to have advantages since it can produce a large size and dimension suitability with the feet used as the models. The purpose of this study was to identify how the craftsman utilizes his body to manually make a precisive shoe last. The research employs the observation method. The authors make observations on the manual process of making shoelast. The research found that pattern making is the first step in making a shoe last. Three techniques of manual shoe last stages are used. They are the strong swing technique to form the basic shape, the light swing technique to form a global shape, and the filing process to form a detailed shoe last.